2009
DOI: 10.1021/bi801654j
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and Glycolytic Cleavage of Etheno and Propano DNA Base Adducts

Abstract: Non-invasive strategies for the analysis of endogenous DNA damage are of interest for the purpose of monitoring genomic exposure to biologically produced chemicals. We have focused our research on the biological processing of DNA adducts and how this may impact the observed products in biological matrixes. Preliminary research has revealed that pyrimidopurinone DNA adducts are subject to enzymatic oxidation in vitro and in vivo and that base adducts are better substrates for oxidation than the corresponding 2′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 63 publications
1
12
0
2
Order By: Relevance
“…Both adducts have been studied as urinary biomarkers9597,137141 in their 2-deoxynucleoside forms. However, as recently observed by Marnett and coworkers, M 1 dG and substituted and unsubstituted etheno adducts are subject to metabolism, presumably in the liver 150153. With regard to etheno adducts, 2-deoxynucleoside forms of G-derived etheno adducts are subject to deglycosylation followed by oxidation of 1, N 2 -ε-G to 2-oxo-1, N 2 -ε-G and of the corresponding substituted adduct, heptanone-1, N 2 -ε-G, to 2-oxoheptanone-1, N 2 -ε-G 153.…”
Section: Nucleic Acid Damage Products As Biomarkers Of Chronic Inflammentioning
confidence: 56%
See 1 more Smart Citation
“…Both adducts have been studied as urinary biomarkers9597,137141 in their 2-deoxynucleoside forms. However, as recently observed by Marnett and coworkers, M 1 dG and substituted and unsubstituted etheno adducts are subject to metabolism, presumably in the liver 150153. With regard to etheno adducts, 2-deoxynucleoside forms of G-derived etheno adducts are subject to deglycosylation followed by oxidation of 1, N 2 -ε-G to 2-oxo-1, N 2 -ε-G and of the corresponding substituted adduct, heptanone-1, N 2 -ε-G, to 2-oxoheptanone-1, N 2 -ε-G 153.…”
Section: Nucleic Acid Damage Products As Biomarkers Of Chronic Inflammentioning
confidence: 56%
“…However, as recently observed by Marnett and coworkers, M 1 dG and substituted and unsubstituted etheno adducts are subject to metabolism, presumably in the liver 150153. With regard to etheno adducts, 2-deoxynucleoside forms of G-derived etheno adducts are subject to deglycosylation followed by oxidation of 1, N 2 -ε-G to 2-oxo-1, N 2 -ε-G and of the corresponding substituted adduct, heptanone-1, N 2 -ε-G, to 2-oxoheptanone-1, N 2 -ε-G 153. With M 1 dG, metabolic and pharmacokinetic studies in rats revealed a biphasic elimination from plasma with M 1 dG found in the urine for more than 24 hr after dosing 150.…”
Section: Nucleic Acid Damage Products As Biomarkers Of Chronic Inflammentioning
confidence: 56%
“…Both adducts have been studied as urinary biomarkers95–97, 137–141 in their 2‐deoxynucleoside forms. However, as recently observed by Marnett and coworkers, M 1 dG and substituted and unsubstituted etheno adducts are subject to metabolism, presumably in the liver 150–153. With regard to etheno adducts, 2‐deoxynucleoside forms of G‐derived etheno adducts are subject to deglycosylation followed by oxidation of 1, N 2‐ε‐G to 2‐oxo‐1, N 2 ‐ε‐G and of the corresponding substituted adduct, heptanone‐1, N 2 ‐ε‐G, to 2‐oxoheptanone‐1, N 2 ‐ε‐G 153.…”
Section: Nucleic Acid Damage Products As Biomarkers Of Chronic Inflammentioning
confidence: 99%
“…However, as recently observed by Marnett and coworkers, M 1 dG and substituted and unsubstituted etheno adducts are subject to metabolism, presumably in the liver 150–153. With regard to etheno adducts, 2‐deoxynucleoside forms of G‐derived etheno adducts are subject to deglycosylation followed by oxidation of 1, N 2‐ε‐G to 2‐oxo‐1, N 2 ‐ε‐G and of the corresponding substituted adduct, heptanone‐1, N 2 ‐ε‐G, to 2‐oxoheptanone‐1, N 2 ‐ε‐G 153. With M 1 dG, metabolic and pharmacokinetic studies in rats revealed a biphasic elimination from plasma with M 1 dG found in the urine for more than 24 hr after dosing 150.…”
Section: Nucleic Acid Damage Products As Biomarkers Of Chronic Inflammentioning
confidence: 99%
“…Many considerable efforts have been focused on the oxidation of DNA and its bases because of their important role in the process of mutagenesis and carcinogenesis as well as cancer therapeutics [1,2]. Guanine is the most easily oxidized bases in DNA and the electrochemical detection of DNA in biological samples is based on the oxidation of guanine [3][4][5].…”
Section: Introductionmentioning
confidence: 99%